Penerapan Strategi Pembelajaran Inovatif pada Mata Pembelajaran Bahasa Indonesia untuk Meningkatkan Literasi Siswa SD Kelas 1 - Aulia Rahmawati; Ibnu Muthi (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
This study aims to examine the implementation of innovative learning strategies in improving the literacy skills of first-grade elementary school students in the subject of Indonesian language. Early literacy serves as a crucial foundation for students’ academic development; however, many lower-grade students have not yet reached the minimum standards in reading and writing. To address this challenge, innovative learning strategies such as shared reading, storytelling, the use of visual and digital media, as well as contextual and simple project-based approaches were employed. This research utilized a Classroom Action Research (CAR) method over two cycles, involving 20 first-grade students. Data were collected through observation, interviews, documentation, and literacy skill assessments. The findings showed a significant improvement in students’ reading, writing, listening, and speaking abilities. The learning process became more enjoyable, participatory, and suited to the cognitive developmental stage of young children. In addition, students' motivation and confidence in using language also increased. The teacher’s role as a facilitator and instructional designer was essential in ensuring the success of these strategies. Therefore, innovative learning strategies have proven effective in enhancing the literacy skills of first-grade students and are recommended for broader implementation.